In vivo measurements of irreversible and reversible transverse relaxation rates in human basal ganglia at 7 T: making inferences about the microscopic and mesoscopic structure of iron and calcification deposits. (19th July 2019) - Balasubramanian, Mukund; Polimeni, Jonathan R.; Mulkern, Robert V.
Abstract : The goal of this study was to measure irreversible and reversible transverse relaxation rates in the globus pallidus and putamen at 7 T, and to use these rates to make inferences about the sub‐voxel structure of iron and calcification deposits. Gradient Echo Sampling of a Spin Echo (GESSE) data were acquired at 7 T on eighteen volunteers spanning a large range of ages (23–85 years), with calcifications in the globus pallidus incidentally observed in one volunteer. Maps of transverse relaxation rates were derived from the GESSE data, and the mean value of these rates in globus pallidus and putamen was estimated for each volunteer. Both irreversible and reversible transverse relaxation rates increased with the expected age‐dependent iron content in these structures, except for the individual with calcifications for whom extremely large reversible relaxation rates but normal irreversible relaxation rates were found in the globus pallidus. Given the sensitivity of irreversible and reversible transverse relaxation rates to microscopic and mesoscopic field variations, respectively, our findings suggest that joint consideration of these rates may yield information not only about the amount of iron and calcification deposited in the brain, but also about the sub‐voxel structure of these deposits, perhaps revealing certain aspects of their geometry and cellular distribution. Abstract : GESSE data were acquired at 7 T on 18 volunteers spanning a large range of ages, with calcifications in the globus pallidus incidentally observed in one volunteer. For the most part, both irreversible and reversible transverse relaxation rates, derived from the GESSE data, increased with the expected age‐dependent iron content in these structures. A striking exception was the individual with calcifications, for whom extremely large reversible relaxation rates but normal irreversible relaxation rates were found in the globus pallidus.